Humoral and cellular immune response and the safety of third SARS-CoV-2 mRNA vaccine with longer interval after the second vaccination in kidney transplant recipients - Takai, Satoshi; Nishida, Hayato; Ito, Hiromi; Fukuhara, Hiroki; Nawano, Takaaki; Narisawa, Takafumi; Kanno, Hidenori; Yagi, Mayu; Yamagishi, Atsushi; Sakurai, Toshihiko; Naito, Sei; Kato, Tomoyuki; et al. (Frontiers in Immunology, 2022)
We evaluated the humoral and cellular immune responses and safety of the third severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccine with a longer interval after the second vaccination in kidney transplant recipients (KTRs). We enrolled 54 kidney transplant recipients without a history of coronavirus disease 2019 (COVID-19), who received a third dose of the vaccine. We assessed anti-SARS-CoV-2 spike antibody and antigen-specific T cells using enzyme-linked immunospot (ELISpot) against the spike protein at baseline, after the second vaccination, and after the third vaccination. We also evaluated the adverse events related to each dose of the vaccine. The duration between the second and third vaccinations was 7 ± 1 month. All 17 (100%) KTRs with anti-SARS-CoV-2 antibody positivity after the second vaccination and 27 of 37 (73%) KTRs without anti-SARS-CoV-2 antibody positivity after the second vaccination were positive for anti-SARS-CoV-2 antibodies (p=0.022). Anti-SARS-CoV-2 antibody titers were significantly higher than those after the second vaccination (p<0.001). Age ≥ 60 years and lymphocyte count < 1150/mm3 were confirmed as risk factors for anti-SARS-CoV-2 antibody negativity after the third vaccination in multivariate regression analysis. ELISpot cytokine activities were positive after the third vaccination in 26 of 29 (90%) KTRs with ELISpot cytokine activity positivity after the second vaccination and 12 of 24 (50%) KTRs without ELISpot cytokine activity after the second vaccination. The rate of change in cytokine activity after the third vaccination was significantly higher than that after the second vaccination (p<0.001). Only lymphocyte counts less than 1150/mm3 were confirmed as risk factors for ELISpot cytokine activity negativity in the multivariate regression analysis. Systemic adverse events classified as greater than moderate did not differ for each vaccine dose. None of the patients showed clinical symptoms of acute rejection. The third SARS-CoV-2 mRNA vaccine administration, with a longer interval after the second vaccination, improved humoral and cellular immune responses to SARS-CoV-2 mRNA vaccines without severe adverse effects in the KTRs.